Let Causatives and (A)symmetric dat‐nom Constructions. (18th July 2014) - Wood, Jim; Sigurðsson, Halldór Ármann
Abstract The verb láta 'let/make' in Icelandic provides a unique opportunity to understand the behavior of symmetric versus asymmetric dat‐nom constructions, as well as the nature of nominative‐accusative case alternations. In this paper, we take a close look at láta and examine a set of cases where dat‐nom verbs are embedded under láta, resulting in the otherwise nominative object becoming accusative in some cases and remaining nominative in others. We propose that phase extension of an Appl head underlies both the availability of accusative in an embedded dat‐nom verb and the possibility of A‐moving a nominative object past the dative to the subject position. We further hypothesize that the base‐generated position of the verbal root in the syntax underlies the lexical difference between symmetric and asymmetric dat‐nom verbs.